PENGARUH TEMUAN AUDIT, TINDAK LANJUT HASIL PEMERIKSAAN, DAN KUALITAS AUDITOR INTERNAL TERHADAP OPINI AUDIT: TINGKAT PENGUNGKAPAN SEBAGAI VARIABEL INTERVENING - Fatimah Nur Jannah, (2022)
The provision of an audit opinion aims to provide an overview of the fairness of the financial statements presented by an entity. Through the audit opinion, the quality of the financial statements can also be seen. This study was conducted with the aim of testing and proving the effect of audit findings, follow-up of audit results, and the quality of internal auditors on the provision of audit opinions by including the level of disclosure of financial statements as an intervening variable. The population in this study were Ministries/Institutions in Indonesia in 2015-2019. The sample in this study was 62 Ministries/Institutions using purposive sampling technique. Data analysis was performed using STATA software version 16.0. The results obtained state that audit findings have a significant effect on the acquisition of audit opinions. Follow-up of audit results and the quality of the internal auditors have no significant effect on obtaining an audit opinion. Disclosure of financial statements cannot mediate the effect of audit findings and follow-up of audit results on obtaining an audit opinion.